Predicting early career productivity of PhD economists: Does advisor-match matter? (2020)
We assess the role played by department rank and advisor-match on the early stage productivity of recent PhDs in economics using a tailor-made data set based on RePEc. After allowing for the potential influence of other factors, including gender and field of specialisation, we find as expected that both advisory quality and rank of the graduation institution are positively related to the academic productivity of graduates. However, in top institutions, students working with the most productive academics do not outperform others unless they co-author with their advisor. For students in non-top institutions, being advised by the best academics is always associated with a higher research output. Possible explanations for this difference are pointed out, including selection and differences in advising styles. © 2019, The Author(s).